Analysis of Compliance with the Application of Service Standards in the COVID-19 Era in 2021 at the Dental and Oral Polyclinic, Diponegoro National Hospital - Ambarani, Eghia Laditra; Suryawati, Chriswardani; Shaluhiyah, Zahroh (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
On March 11, 2020, WHO officially declared COVID-19 as a pandemic. The fast-spreading virus has a very large impact on society, from politics, economics, society, security as well as welfare. As health worker dentist has a high risk of getting infected by COVID-19. It is known that the practice of dentists is closely related to the production of aerosol, which is a risk of transmission of COVID-19 infection. Diponegoro National hospital also provides dental services during COVID-19. It is important to know the compliance of dentists and dental nurses in carrying out standard health services at dental and oral polyclinic Diponegoro National hospital during COVID-19. This study is observational research with a qualitative method. The research subject was as many as 17 informants. Collecting data was done by deep interviews and checklist observation. Data were analyzed using content analysis by collecting data, data reduction, presentation of the data, and conclusions. The results of this study show that the compliance of dentists and nurses at Rumah Sakit Nasional Diponegoro in health service standards during COVID-19 is good but not optimal due to the length of time required infrastructure to support health services during COVID-19, from the patient itself, and officer negligence. Abstrak: Pada tanggal 11 Maret 2020, WHO secara resmi mendeklarasikan COVID-19 sebagai pandemi. Virus Corona yang menyebar dengan cepat ini berdampak sangat luas, mulai dari politik, ekonomi, sosial, keamanan, serta kesejahteraan masyarakat. Sebagai tenaga kesehatan, dokter gigi memiliki resiko tinggi terinfeksi COVID-19. Diketahui bahwa aktivitas dokter gigi sangat erat berhubungan dengan produksi aerosol yang merupakan resiko penularan infeksi COVID-19. Rumah Sakit Nasional Diponegoro juga menyediakan pelayanan gigi selama COVID-19. Maka penting untuk mengetahui kepatuhan dokter gigi dan perawat gigi dalam melakukan standar pelayanan kesehatan di poli gigi dan mulut selama COVID-19. Penelitian ini merupakan penelitian observasional dengan metode kualitatif. Subjek dari penelitian ini sebanyak 17 informan. Pengumpulan data dilakukan dengan wawancara mendalam dan observasi check list. Data dianalisis dengan metode content analysis dengan tahapan pengumpulan data, reduksi data, penyajian data, dan menarik kesimpulan. Hasil dari penelitian ini menunjukkan bahwa kepatuhan dokter gigi dan perawat gigi di Rumah Sakit Nasional Diponegoro dalam pelayanan standar kesehatan selama era COVID-19 sudah baik namun belum optimal dikarenakan lamanya tersedia sarana prasarana yang dibutuhkan selama COVID-19, dari sisi pasien, serta dari kelalaian sumber daya manusia.